The Transitus of the Soul and the Intercession of the Angels in Old English Resignation A 49b-56 - Gabriele Cocco (Filologia Germanica)
Resignation (A+B) is still a subject of debate as to its textual unity and classification. Though it is usually partnered to the Old English elegies, Resignation A (ll. 1-70) bears more affinities with penitential poetry. The poem also echoes death liturgy. The invocation geoca mines gæstes (‘save my soul’, 46a) anticipates the soul’s longing not to be captured by demons (49b-53). The plea for angels to lead her at the transitus recurs in antiphons, responsories, and prayers in the Agenda mortuorum of pre-Conquest manuscripts such as the Leofric Missal, the Missal of Robert of Jumièges, the Red Book of Darley, and the Winchcombe Sacramentary. The paper aims to confirm that Resignation A is a penitent’s prayer, whose poet is well learned both in liturgy and theology.